A system for supply chains diversification and (re)design: supporting managers' perspective in the face of uncertainty. Issue 2 (2019) - Longo, Francesco; Nicoletti, Letizia; Padovano, Antonio
Because of the stochasticity of the supply chain (SC) and the increased uncertainty due to the negative trend of the publishing industry that is trying to survive to new trans-media contents delivery, business firms are looking for advanced tools supporting them in (re)defining their business (diversification) and in (re)designing their own SC. Here, a multi-method, iterative, four-step procedure has been defined where a new and win-win integration between value stream mapping (VSM) and multi-paradigm simulation is achieved. Such framework is implemented into a DSS (called SmartDistr), equipped with dedicated GUIs that drive the user along its application and use. The potentials of the proposed approach are demonstrated through the case study of a business firm managing a regional distribution network in the publishing industry. To this end, the proposed case study shows how the SmartDistr DSS allows evaluating operational and financial performance measures along with managerial insights that enable managers to discern easily different business diversification and SC (re)design scenarios.